Judicial populism or a wise measure to speed up the proceedings for failure to provide family assistance? The proposal to grant civil judges the competence to open criminal proceedings against defaulting parents - Gómez Vargas, Ángel (2018)
This article reflects, from a constitutional and procedural pers-pective, on the proposal of Dr. Duberlí Rodríguez Tineo (2018) regarding reform to grant civil judges criminal jurisdiction, so that, in the same court, they process the civil proceeding, esta-blish the pension, and these are empowered to open the criminal proceeding to parents who fail to comply with their economic obligation. This innovation aims to lighten the procedural bur-den of the criminal courts of the 35 Superior Courts of Justice of the country and, thereby, restore the confidence of judicial users in the Judiciary.